The association mental health of adolescents with economic impact during the COVID-19 pandemic: a 2020 Korean nationally representative survey - Hanul Park; Kang-Sook Lee (BMC, 2023)
Abstract Background COVID-19 has affected innumerable aspects of life, including education, economy, and religion. Economic problems and inequality are associated with poor mental health in adolescents. This study aimed to identify the relationship between economic damage to families due to COVID-19 and various mental health problems in Korean adolescents and to evaluate the risk factors of mental health. Methods In total, 54,948 Korean adolescent students from 398 middle and 395 high schools were surveyed between August and November 2020. Complex sample logistic regression was performed to calculate odds ratios (ORs) and 95% confidence intervals (CI) for depression and suicidal ideation, respectively. A generalized linear model analysis was used to examine the association between mental health (unhappiness, loneliness, and stress) and the economic impact of COVID-19. Analyses were adjusted for age, gender, school grade, perceived academic achievement, perceived family economic status, and economic support. Results The ORs of depression (OR = 1.77, 95% CI:1.57-2.00), suicidal ideation (OR = 2.14, 95% CI:1.84-2.50), unhappiness (OR = 1.51 95% CI 1.42-1.60) and lonely (OR = 1.38 95% CI 1.27-1.49) for the low level of perceived family economic status was higher compared to middle level. Adolescents who experienced economic deterioration in their households as COVID-19 showed a higher risk of depression (OR = 1.42, 95% CI:1.35-1.49), suicide ideation (OR = 1.36, 95% CI:1.28-1.44), unhappiness (OR = 2.23 95% CI 2.19-2.27), lonely (OR = 1.20 95% CI 1.17-1.22), and stress (OR = 1.14 95% CI 1.12-1.16) than those who did not. Conclusions The findings revealed an association between the decline in household economic status due to COVID-19 and mental health problems, such as stress, loneliness, suicidal ideation, depression, and unhappiness.